2008
DOI: 10.1111/j.1863-2378.2007.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Surveillance of salmonella in the Faeces of Pigs in Japan

Abstract: The prevalence of faecal carriage of salmonella in 5393 pigs reared on 218 pig farms located in 31 of 47 prefectures in Japan over the period July 2003 to June 2005 was investigated. We isolated 172 strains belonging to 20 serovars and one untypable Salmonella enterica from 169 pig faecal samples (3.1%) collected from 48 farms (22.0%). The most prevalent type of S. enterica was untypable O4,12:d:- which lacks phase 2 flagellar antigen, representing 29.1% (50/172) of all isolates. Of 26 S. enterica serovar Typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…A number of studies have reported similar high Salmonella prevalence in farm animals usually slaughtered for food. Kishima et al [14] reported the isolation of 172 strains of Salmonella from 218 pig farms in Japan. In Australia, Duffy et al [15] reported 46.3% Salmonella species isolation from the faeces of goat.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported similar high Salmonella prevalence in farm animals usually slaughtered for food. Kishima et al [14] reported the isolation of 172 strains of Salmonella from 218 pig farms in Japan. In Australia, Duffy et al [15] reported 46.3% Salmonella species isolation from the faeces of goat.…”
Section: Discussionmentioning
confidence: 99%
“…At a Japanese pig farm, S. Typhimurium infection has been shown to cause both clinical and subclinical cases [3,14]. The effect of dietary lactic acid in controlling clinical S. Typhimurium infections under experimental infection conditions have not been demonstrated either.…”
mentioning
confidence: 99%
“…The incidences of Salmonella spp. detected from swine fecal samples in the USA and Japan were only 4.9% and 3.1%, respectively (Bahnson et al, 2006;Kishima et al, 2008). In one Korean study, Salmonella incidence was reported at 9.5% from fecal samples (Kim et al, 2001).…”
Section: Discussionmentioning
confidence: 99%